Ansiedad y depresión en tiempos de Covid-19 en adolescentes del “Colegio de Bachillerato Hernán Gallardo Moscoso” - Carrillo Obando, Karen Gabriela (2023)
Anxiety and depression are diseases that have currently become very relevant public health problems in the population, especially in one of the most vulnerable and affected groups in the health area, adolescents, due to the biological-psychosocial changes typical of adolescence, many of which generate crises, conflicts and contradictions, much more so in the context of Covid-19 where their lifestyle has been modified. An investigation was carried out at the Hernan Gallardo Moscoso High School, with the purpose of determining, through the Hamilton Tests of Anxiety and Depression respectively, the prevalence and level of these psychological disorders. A descriptive, deductive-inductive and synthetic analytical study was carried out with both holistic and health promotion approaches in a sample of 76 students, obtaining as results that 79% of the students present a degree of anxiety and regarding to depression, 38% present depression at different levels. It was determined that most adolescents do not present depression and have anxiety at a mild level; however, an educational proposal was developed to improve the mental health of students